CASH FLOW STATEMENT ANALYSIS OF BINJAI CITY GOVERNMENT’S - Khairi, Rajwa; Abi Setiawan, Muhammaad; Muda, Iskandar (JIAR : Journal Of International Accounting Research, 2025)
This study aims to analyze the performance of the Binjai city government in managing regional cash in 2023. The research data is quantitative and taken from the official website of the Binjai city government. The analysis method used is the horizontal technique, namely comparative trend analysis. This study analyzes the trends in Binjai City's cash flow reports based on four activities, namely operating activities, investing activities, financing activities, and transitional activities. The results of the analysis show very strong operational performance, marked by an increase in net cash flow from operating activities of nearly 15% from the previous year and a high commitment to infrastructure development, which resulted in an increase in the net cash flow deficit from investing activities of nearly 20%. In terms of financing, the analysis results show a conservative fiscal policy, as evidenced by an increase in the net cash flow deficit from financing activities of 6.51% from the previous year for debt repayment. Therefore, the total net cash flow in 2023 is in deficit and has decreased by around 177% from the previous year. This is a challenge for the Binjai city government.